Stories of Violence: a Narrative Criminological Study of Ambiguity - Sandberg, Sveinung (The British journal of criminology, 2015)
Violence features in human life, not only as actual physical confrontation but also as stories. Stories of violence are particularly important in violence-prone subcultures and among those partaking in the illegal drug economy. Drawing on narrative analysis, this study examines stories of violence among a population of incarcerated Norwegian drug dealers. Four widespread story types are identified: business narratives, intimidation narratives, moral narratives and survivor narratives. We explore the content of these stories and the work they do for tellers while keeping a keen eye on their ambiguous nature. We argue that stories and storytellers plurivocality is often missed when stories of violence are described within established criminological traditions.